Numerical simulation of HEMT devices - Ng, Jun Hao. (2013)
This report documents the progress made during the course of the final year project. After acquiring the Silvaco software, time was spent to learn the functions and to understand the complex coding involved. Simulations were run using samples and the results were analysed. These were done in preparation for future simulations of customised devices. Having a strong foundation is important in easing the progress later. Furthermore, the report also provides background information on the physics of high electron mobility transistors and the various types of such transistor. This report also includes a literature review on the several studies that have been done on HEMTs. An introduction to the software Silvaco is also included with explanations on the functions used during the course of the project. Simulations that were run using the software are also included in this report. Images and explanations are available as well. The conclusion will also touch on future developments of the project and how progress can be made in the project.